PELATIHAN PERANCANGAN MENU BAGI UMKM KULINER - Yoanita Alexandra; Nosica Rizkalla; Septi Fahmi Choirisa (Jurnal Sinergitas PKM & CSR, 2022)
The Covid-19 pandemic had a significant impact on the Indonesian economy, including MSME business players. In the Indonesian economy, Micro, Small and Medium Enterprises or MSMEs are the business groups that have the largest number. The menu in the culinary business is an important component for business success. The menu structure plays important role in the level of sales, therefore it must be made attractively and appropriately. For this reason, basic knowledge is needed to support menu preparation, such as knowledge of the type of food provided, framework, character, composition, design and menu writing. This activity is a Community Service activity that is integrated with the Menu Planning course (menu planning) majoring in Hospitality. The Community Service Partners are five culinary MSMEs located in the Tangerang and Bogor areas. The implementation of activities is carried out directly or by interview with culinary MSME entrepreneurs. The results of this activity are in the form of observation reports and recommendations for menu design for culinary businesses. This activity is useful for culinary entrepreneurs to be able to analyze business progress and the need for changes in terms of menus. In addition, careful menu planning can have an impact on culinary businesses becoming more operationally and financially efficient.abstract in bahasaPandemi Covid-19 membawa dampak yang signifikan bagi perekonomian Indonesia, tak terkecuali para pelaku bisnis UMKM. Dalam perekonomian Indonesia, Usaha Mikro, Kecil, dan Menengah atau UMKM adalah kelompok usaha yang memiliki jumlah paling besar. Menu dalam usaha kuliner merupakan komponen penting bagi keberhasilan usaha. Susunan menu sangat berperan dalam tingkat penjualan, maka dari itu harus dibuat secara menarik dan tepat. Untuk itu diperlukan pengetahuan dasar sebagai penunjang dalam penyusunan menu, seperti pengetahuan tentang tipe makanan yang disediakan, kerangka, karakter, komposisi, design serta penulisan menu. Kegiatan ini merupakan kegiatan Pengabdian Kepada Masyarakat yang terintegrasi dengan mata kuliah Menu Planning (Perencanaan menu) jurusan Perhotelan. Mitra Pengabdian adalah lima UMKM kuliner yang terletak di daerah Tangerang dan Bogor. Pelaksanaan kegiatan dilaksanakan secara langsung ataupun dengan interview dengan pengusaha UMKM kuliner. Hasil dari kegiatan ini berupa laporan observasi serta rekomendasi perancangan menu bagi usaha kuliner. Kegiatan ini bermanfaat bagi pengusaha kuliner untuk dapat menganalisa progress usaha dan kebutuhan perubahan dari segi menu. Selain itu, perencanaa menu yang matang, dapat berdampak terhadap usaha kuliner menjadi lebih efisien secara operasional maupun finansial.